Antenatal diagnoses of congenital cataracts and related surgical complications in a familial case of Nance-Horan Syndrome - Gayathri K Sivakumar; Gunjan Mhapankar; Victoria Mok Siu; Sapna Sharan (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
We describe rare cases of Nance-Horan Syndrome (NHS) in two brothers with antenatal diagnoses of hyperechoic crystalline lenses and postnatal findings of bilateral dense nuclear cataracts, microphthalmia, and absent red reflexes. Here, we present the first case report to discuss the diagnosis and the intraoperative and post-operative sequelae of cataract extraction in pediatric patients with NHS.